Toward Fair and Freedom-Respecting Assessments in Africa - (:unkn) unknown (My University, 2024)
In the African context, where digital infrastructures are unevenly distributed, the monitoring of remote assessments presents significant challenges. The Université Numérique Cheikh Hamidou Kane (UNCHK), with over 70,000 students, served as a case study to analyze these issues. Currently, exam monitoring is conducted by human proctors using tools such as Zoom and Safe Exam Browser. However, the introduction of artificial intelligence (AI) is being considered to enhance the integrity of assessments, raising critical questions about equity and data privacy. Drawing on Fabio Zanzotto's work on humanizing AI, this paper explores the potential of a hybrid monitoring model where AI assists human proctors while leaving final decisions to them. A survey conducted among students revealed that 56% face difficulties accessing digital infrastructure, thereby exacerbating inequalities during monitored exams. This study offers a reflection on how collaboration between AI and human monitoring could address the unique challenges of the continent while ensuring fairer assessments that respect individual freedoms.
Keywords: African Research